Digital Linguistic Markers of Emotions As of the September 2024 Hostilities in Lebanon: A Case Study in Communication Arts Course at a University Level in Southern Lebanon - Joudi, Nadine Sami; Ayoub, Nawal Nabih (European Scientific Journal, ESJ, 2025)
Language and emotions are intricate systems that have several interactions. Amid the expeditious spread of digitalization and the upswing of various international issues, this case study seeks to explore how students at the Lebanese University in the South utilize language on social media to convey their emotions as of the 2024 clashes and airstrikes in Lebanon. Further, it aims to identify digital linguistic markers that reflect key emotional states and social identity. Drawing on discourse analysis which acknowledges language as a dynamic system that is influenced by shared experiences, values, and beliefs, and importantly, by Conceptual Act Theory which explores how meaning is constructed from experiences and perceptions and on sentiment analysis, a mixed-methods approach is employed. A convenient sampling of (191) university EFL students taking the Communication Arts module during the fall semester of 2024-2025 complete an online survey of 15 multiple choice and Likert scale items. Twelve students joined a focus group discussion and 155 out of 191 participants interacted on the web-based application, Padlet. The findings show that utilizing language in the context of social media platforms through words, emojis, hashtags, slogans, or posting articles, images, or videos, plays a vital role not only in channelling positive and negative sentiments in a constructive way, but also in signaling to belong to a collective identity during times of crisis in Lebanon. The overall analysis indicated that using various linguistic practices on social media platforms communicates positive and negative emotions, and upholds social norms and ideologies.